ENDOMETRIAL THICKNESS ASSESSED BY TRANSVAGINAL ULTRASOUND AS A PREDICTOR OF THE RISK OF ENDOMETRIAL CANCER AND ATYPICAL ENDOMETRIAL HYPERPLASIA IN ASYMPTOMATIC POSTMENOPAUSAL PATIENTS - Tanturovski Mile; Jovanovska, Viktorija; Stojovski Marjan; Tanturovski Dragan; Stojchevski Sasho; Aluloski Igor; Zafirova Ivanovska Beti (Macedonian association of anatomists and morphologists, 2020)
ABSTRACT Introduction: Endometrial cancer (EC) is the most common gynecological malignancy in the developed world. It is estimated that 320000 new cases are diagnosed annually, accounting for up to 6% of all newly diagnosed malignant neoplasms. In spite of the associated controversies, transvaginal sonography and measurement of endometrial thickness are wellaccepted, standard procedures in many gynecological office visits to date. Objective: The study aim was to determine the diagnostic performance of endometrial thickness measured by transvaginal sonography in diagnosing endometrial cancer and atypical endometrial hyperplasia in asymptomatic postmenopausal patients. Materials and methods: The databases of the Department of gynecological oncology at the University Clinic of Gynecology and Obstetrics in Skopje, in the period January – December 2015 were searched to identify asymptomatic postmenopausal patients undergoing endometrial sampling due to increased endometrial thickness. Results: A total of 268 patient records that met the criteria were identified. The prevalence of endometrial cancer and atypical endometrial hyperplasia in the study were 5.2% and 2.2%, respectively. Endometrial thickness was a statistically significant independent predictor of the presence of endometrial cancer and atypical endometrial hyperplasia (p<0.001). The ROC curve analysis in our study had an AUC of 0.8 and identified a cut-off level to be ≥10mm which was associated with a sensitivity of 85.7%, specificity of 60.6%, PPV of 10.7% and NPV of 98.7% for the detection of endometrial cancer. Conclusion: The proposed cut-off of ≥10mm for discriminating between “normal” and “pathological” endometrial thickness is clinically reasonable and of moderate diagnostic value. However, the cut-off value does not achieve the required high sensitivity with clinically acceptable low false positive rates. Nevertheless, transvaginal sonography for measuring endometrial thickness can be used to exclude pre-malignancy or malignancy in asymptomatic postmenopausal women with risk factors because of its low false negative rate.
Keywords: endometrial cancer; atypical endometrial hyperplasia; endometrial thickness; asymptomatic postmenopausal patients.